Preparing Your Paper in LATEX for Nepalese Journal of Civil Engineering - Shrestha, Jayandra Raj; Sharma, Bishnu (Nepal Journal of Civil Engineering, 2021)
This is a working template for the research article for Nepalese Journal of Civil Engineering. The template has been typeset in LATEX. You have to replace certain sections of this template by your content and produce a pdf file as final output. Format for different types of elements that could occur in the paper are already defined in this template. The authors are to strictly follow the style/formatting as defined in this template for consistencies in a single paper and across different papers. The contents of the paper appears in a two column format, with an exception of the paper title, author names, affiliations, abstract and keywords. Your paper should be limited to 8 pages and abstract should not exceed 300 words. Each of the keywords need to be separated by commas as given in the example below.